PERAN DAN STRATEGI HUMAS (PUBLIC RELATIONS) DALAM MEMPROMOSIKAN PRODUK PERUSAHAAN - Ardhoyo, T. E. (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
The basic role and function of public relations ares: Images maker, Communicater/ mediator, and Backup Management. Promotion is one components of the marketing mix used by a company to communicate with their market, customers or possible customers. Public Relations plays it’ s role to promote the company’s products. The purpose of descrip is to discuss the Public Relation’s role and strategy in promoting the company’s products. The method used library research with the descriptive explorative approaches. It can be concluded that: (1) The role of public relations is significantly support the management to promote the company’s products. (2) The PR strategy is effective in promoting the company’s products through activities such as publicity, trade promotion event, sponsorship and others.